Comparative Efficacy of English-Only Policies and Multilingual Scaffolding: A Meta-Synthesis of Language Proficiency Outcomes - Resheil Sellote; Caren Mae Duterte; Abegail Dante (Journal of Language Development and Linguistics, 2026)
This qualitative meta-synthesis aims to examine the comparative impact of English-Only Policy (EOP) and multilingual scaffolding on student language proficiency. The core concepts investigated include fluency, comprehension, learner confidence, and classroom engagement. Utilizing a document analysis framework and thematic coding, the methodology synthesizes data from peer-reviewed ESL and EFL studies published between 2015 and 2025. Results reveal that EOP significantly improves oral fluency and structural accuracy but poses affective challenges for low-proficiency learners. Conversely, multilingual scaffolding effectively facilitates conceptual understanding and engagement but may not resolve foundational language deficits. The study concludes that both approaches are complementary, advocating for a context-responsive, hybrid instructional model that integrates both strategies to foster optimal and sustainable language acquisition outcomes.